1970
DOI: 10.1111/j.1471-0528.1970.tb03541.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Hypertrophy in Severe Pregnancy Anaemia*

Abstract: A prospective combined study of consecutive patients with severe pregnancy anaemia (haemoglobin value less than 8 g. per 100 ml.) was performed in five countries to determine the relationship between maternal anaemia and placental weight. Data were recorded in 732 pregnancies and the important finding was that placental hypertrophy was associated with maternal anaemia in all centres. There was a positive correlation between maternal anaemia and placental weight which was statistically highly significant; Melbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 13 publications
2
52
1
Order By: Relevance
“…In human pregnancies, an increased placental ratio is associated with maternal anemia [5,21,22], smoking [5,23], and gestational diabetes mellitus [14], factors that are related to the supply of nutrients. In rats given a calorically balanced diet, a reduction in protein intake from 18 to 9% was associated with an increase in the placental ratio [24].…”
Section: Discussionmentioning
confidence: 99%
“…In human pregnancies, an increased placental ratio is associated with maternal anemia [5,21,22], smoking [5,23], and gestational diabetes mellitus [14], factors that are related to the supply of nutrients. In rats given a calorically balanced diet, a reduction in protein intake from 18 to 9% was associated with an increase in the placental ratio [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mongia et al 8 in his study observed that decreased placental weight in low haemoglobin concentration, similar to the present study. But Beischer et al 9 and Lao et al 10 in their study observed that the maternal anaemia was associated with placental hypertrophy.…”
Section: Discussionmentioning
confidence: 88%
“…This is shown by re duced birth weights in women with anemia [1,2], living at high altitudes [3], and with raised carboxyhemoglobin levels through cigarette smoking [2,4]. Similar growth re tardation can be induced in animals through exposure to carbon monoxide (CO) [5] or low partial pressures of oxygen [6,7], and through maternal hemorrhage early in preg nancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similar growth re tardation can be induced in animals through exposure to carbon monoxide (CO) [5] or low partial pressures of oxygen [6,7], and through maternal hemorrhage early in preg nancy [8]. Paradoxically however, despite obvious damage to the fetus, placental growth is frequently enhanced perhaps to compensate for an otherwise reduced oxygen supply to the fetus [1,5,7,8].…”
Section: Introductionmentioning
confidence: 99%